PARENT INVOLVEMENT PROGAM FOR TEACHER - Prayogo Prayogo (Deiksis, 2011)
Parent Involvement program for Teacher is a program with a family approach as a part of the educational system of children. Teachers and parents have an important role in children’s education through communication. The key of communication is awareness and sensitivity. The aim of this paper is to give an understanding of parents empowerment as an asset in educating children through the role of the teacher. The method is used in this paper is qualitative by collecting data. Teacher not only teach but also empower parent s as one of golden rule in children’s education. Teachers are led to face numerous families through professionalism, ability and confidence to increase parent involvement in children’s education. Parent involvement in children’s education absolutely must be done, so effective communication support for teachers to parents through direct involvement, demonstration or display and communication so that the relationship between parents and teachers can give a good impact for children. The ability to resolve difficulties with parent involvement can be resolved through ability confidence, and lead to a productive impact.Keywords : Parent Involvement Progam, Communicate, Teacher, Empowement Parent.